An optimization method of multi-objective evacuation path for off-site emergency under severe nuclear accidents. (1st September 2022) - Tang, Zhihong; Xie, Xingwen; Cai, Jiejin; Li, Qiong
Highlights: Multi-objective evacuation route optimization method was proposed. It is suitable for off-site emergency evacuation under severe nuclear accidents. The simulation was carried out under the hypothetical accident of HPR1000. Abstract: The emergency evacuation path planning measures of nuclear power plants can quickly protect the people from orderly evacuation and effectively prevent the effects of radiation. This paper proposes a multi-objective evacuation path optimization method for off-site emergency evacuation under severe nuclear accidents. This method combines the atmospheric dispersion model, the improved ant colony algorithm and the road resistance model to solve the evacuation path with the least travel time and radiation dose, and introduces the cancer risk probability caused by radiation into the evaluation process. The radiation environment generated by the Monte Carlo method and the hypothetical nuclear accident situation of HPR1000 were respectively optimized for the evacuation path planning under the conditions of nuclear emergency. The results show that the method can obtain multiple reasonable evacuation paths, and can effectively provide decision support for the early emergency response to nuclear accidents, and choose different focused plans.